Oral tradition and identity of West Kalimantan society - Chairil Effendi (Universiti Kebangsaan Malaysia, 2009)
This article is an overview of oral tradition in Sambas, Sekadau and Ketapang in North, Central and South of West Kalimantan, representing three relatively different cultural regions. Discourse of their identity labeling is based on the plurality of the Dayak and Malays, who share political powers, despite religious differences between them. It is their social interactions with other ethnic groups in West Kalimantan that enrich the cultural and religious plurality in the region